Ca2+/Calmodulin-Dependent Protein Kinase II Regulation by Inhibitor 1 of Protein Phosphatase 1 Protects Against Myocardial Ischemia–Reperfusion Injury. (September 2019) - Yu, Jin; Chen, Yun; Xu, Mengting; Sun, Linlin; Luo, Huiqin; Bao, Xiaofeng; Meng, Guoliang; Zhang, Wei
Ca 2+ /calmodulin-dependent protein kinase IIδ (CaMKIIδ) plays a vital role in cardiovascular system. However, the potential protective role of inhibitor 1 of protein phosphatase 1 (I1PP1), which can regulate CaMKII, on myocardial ischemia–reperfusion (I/R) injury remains unknown. In the present study, expression of CaMKIIδ variants was detected by quantitative real-time polymerase chain reaction. I1PP1 was overexpressed by pericardial injection of recombinant adenovirus. Two weeks later, rats were subjected to left anterior descending ligation for 30 minutes followed by reperfusion. Myocardial infarct size was assessed by Evans blue/triphenyl tetrazolium chloride staining. Serum creatine kinase (CK) and lactate dehydrogenase (LDH) activity as well as myocardial pathological structure were detected. CaMKII activity was evaluated by phosphorylation of phospholamban (PLB) and oxidation of CaMKII. Expression of dynamin-related protein 1 (DRP1) and optic atrophy 1 (OPA1) in the mitochondria was measured by Western blot. We found that CaMKIIδA and CaMKIIδB expression decreased, while the expression of CaMKIIδC increased after myocardial I/R. Moreover, after 30-minute ischemia followed by 6 hours of reperfusion, I1PP1 overexpression reduced myocardial infarct size, decreased serum CK and LDH activity, ameliorated myocardial pathological structure, inhibited PLB phosphorylation at Thr17, suppressed CaMKII oxidation, elevated CaMKIIδA and CaMKIIδB variants but reduced CaMKIIδC variants, attenuated myocardial oxidative stress, improved myocardial mitochondrial ultrastructure, increased mitochondrial number and mitochondrial DNA copy number, and decreased DRP1 but increased OPA1 protein expression from the mitochondria in rats. Thus, I1PP1 regulated CaMKII, protected mitochondrial function, reduced oxidative stress, and attenuated myocardial I/R injury.